Utilization of hemp (Cannabis sativa L.) as an alternative raw material for the production of three-layered particleboard - Ryan Moulana (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
As the availability of high quality trees decreased and the price increased the wood base panel industry is looking to replace the common used wood by agricultural residues or fast growing trees and plants as well as agricultural plants like hemp (Cannabis sativa L.). Hemp offers characteristics that are similar to wood properties. In line with this research, three-layered particleboards under utilization of hemp material were developed. The hemp was used in combination with industrial produced particles to find out which amount of wood can be substituted by hemp and further to investigate which decreased densities can be realized by the use of hemp. Hemp can be used for the production of lightweight particleboards due to its lower bulk density compared to wood. All developed hemp/wood based particleboards were produced under industrial parameters in laboratory and pilot scale using conventional urea formaldehyde-resin, hardeners, and hydrophobic substances. The mechanical technological properties of all produced innovative particleboards and reference particleboards were determined according to current DIN/EN standards. In detail density profile, bending strength, internal bond strength, surface strength, and thickness swelling were determined. Compared to the produced reference particleboards, consisting only of wood particles, the developed hemp/wood particleboards possessed better mechanical-technological properties. Furthermore it was realized to produce particleboards with densities of 550 kg/m³ by using hemp due to its low bulk density which fulfills the given DIN/EN requirements. As an overall result we found out that hemp is a real alternative to nowadays used wood for the production of particleboards in general and for the production of lightweight particleboards in particular.